Proceedings of the 12th International Conference on Information Integration and Web-Based Applications &Amp; Services 2010
DOI: 10.1145/1967486.1967615
|View full text |Cite
|
Sign up to set email alerts
|

The key success factors to mobile commerce for Arab countries in Middle East

Abstract: A number of studies have been conducted on the diffusion of mobile commerce, its challenges, opportunities, issues and obstacles. However, few have emphasized on its adoption within Middle East countries. This paper reviews the current literature in order to assess the mobile commerce adoption in Arab countries within Middle East and identify the key success factors in mobile commerce adoption in them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Thus, despite the rapid growth of e-commerce and mobile services, consumers in the Middle East have not completely understood the mechanism of mobile payments. In addition, they are most likely not willing to use mobile commerce out of their fear of their personal privacy and financial security being compromised (Al-Hosni et al , 2010). Reviewing the relevant literature, this paper will build on past studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite the rapid growth of e-commerce and mobile services, consumers in the Middle East have not completely understood the mechanism of mobile payments. In addition, they are most likely not willing to use mobile commerce out of their fear of their personal privacy and financial security being compromised (Al-Hosni et al , 2010). Reviewing the relevant literature, this paper will build on past studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There had also been limited coordination between private and public sectors to provide m-commerce services. However, many Middle Eastern countries have recently been starting to open their mobile markets to new operators to create more mature markets (Alhosni et al, 2010). For instance, in 2012, PayPal partnered with Aramex to launch its operations in the Middle East (Farhat, 2014).…”
Section: M-payments In the Middle East And Arab Countriesmentioning
confidence: 99%
“…Significantly, Middle Eastern Arab countries 2 , which are considered the second fastest growing region (after the US and Canada) in mobile and telecommunication adoption, have been experiencing m-payments services and applications since 2003 through different marketing and technological strategies (Alhosni et al, 2010). However, no sufficient level of consumer satisfaction has yet been achieved (Alhosni et al, 2010;and others), and many m-commerce applications have failed to meet consumers" expectations (Bhatti, 2008). Although several studies indicated the importance of trust for consumers to accept and use m-payments in the Middle Eastern Arab region (e.g.…”
Section: Research Introduction and Motivationmentioning
confidence: 99%
“…Although several studies indicated the importance of trust for consumers to accept and use m-payments in the Middle Eastern Arab region (e.g. Alhosni et al, 2010;and others), trust in m-payments in this region has not yet been sufficiently empirically studied.…”
Section: Research Introduction and Motivationmentioning
confidence: 99%
See 1 more Smart Citation